1998
DOI: 10.1002/(sici)1521-186x(1998)19:2<123::aid-bem11>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A 0.5 G, 60 Hz magnetic field suppresses melatonin production in pinealocytes

Abstract: The objective of this study was to develop a model for testing various hypotheses concerning possible mechanisms whereby electromagnetic fields might induce suppression of nighttime melatonin production in rodents. A published method for digesting freshly obtained pineal glands to the single cell level was modified, yielding better than 95% viability. An in vitro exposure facility developed for the Food and Drug Administration was used for 12-h overnight exposures of primary pinealocyte cultures to 0.05 mT, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
10
0
2
Order By: Relevance
“…If, as previously proposed by Rosen et al [1998] andBrendel et al [2000], MF can exert its action directly on the mammalian pineal gland, a relatively short high intensity stimulus such as that administered here, should be capable of altering melatonin production in a consistent and reproducible manner. If, however, the effects of MF on pineal melatonin levels are mediated by another part of the circadian system or require the presence of an intact circadian axis [Olcese et al, 1988;Olcese, 1990], these effects may not be demonstrable in the isolated pineal.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…If, as previously proposed by Rosen et al [1998] andBrendel et al [2000], MF can exert its action directly on the mammalian pineal gland, a relatively short high intensity stimulus such as that administered here, should be capable of altering melatonin production in a consistent and reproducible manner. If, however, the effects of MF on pineal melatonin levels are mediated by another part of the circadian system or require the presence of an intact circadian axis [Olcese et al, 1988;Olcese, 1990], these effects may not be demonstrable in the isolated pineal.…”
Section: Resultssupporting
confidence: 51%
“…In the current article, we have developed a technique which facilitates the analysis of the in vitro effects of MF on cultured organs in a highly controlled manner and which enables monitoring of changes in hormone secretion with a high degree of temporal resolution. While progress has been made in previous studies [Rosen et al, 1998;Brendel et al, 2000] to provide models which accurately reflect the natural situation by using cultured organs and monitoring their response to MF over a time course, here we believe we have employed the most highly controlled system to date. Importantly, this system also allows the remote collection of samples during experimentation, therefore, removing the potential confounding effects associated with manual collection of timed samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been carried out at frequencies in the ELF range, using various exposure paradigms. In primary pinealocyte cultures exposed in vitro to 60 Hz 0.05 mT vertical AC and 0.06 mT DC fields, melatonin production declined by almost 50% [Rosen et al, 1998], but in vivo studies of melatonin and other neurohormones revealed either increases [Lerchl et al, 1998;Zecca et al, 1998], decreases [Burch et al, 1999[Burch et al, , 2000Karasek et al, 1998;Reiter et al, 1998;Juutilainen et al, 2000], or no changes [Selmaoui et al, 1997;Truong and Yellon, 1997;Graham et al, 2000]. Pulsed microwave exposure at up to SAR 0.3 W/kg did not disrupt the normal circadian profile of melatonin or other hormones of the hypothalamo-pituitary-adrenal axis de Seze et al, 1998de Seze et al, , 1999, with the only exception of a commercial dairy herd kept in close proximity to a short wave (3-30 MHz) radio transmitter station.…”
Section: Effects On Neurohormonal Secretionmentioning
confidence: 98%
“…Most of the results concentrate on influence of EMF on secretion of hormone in brain. It is well known that exposure to ELF-MF may suppress the synthesis of the indoleamine hormone melatonin in the pineal gland of some species [7][8][9]. This effect of ELF-MF on pineal function is similar to that of light, which is the main environmental cue mediating the response to photoperiod in mammals and birds.…”
Section: Introductionmentioning
confidence: 99%